COVID-19 Pandemic Uncertainty Shock Impact on Macroeconomic Stability in Ethiopia - DEMIESSIE, Habtamu Girma (Journal of Advanced Studies in Finance, 2020)
This study investigated the impact of COVID-19 pandemic uncertainty shock on the macroeconomic stability in Ethiopia in the short run period. The World Pandemic Uncertainty Index (WPUI) was used a proxy variable to measure COVID-19 Uncertainty shock effect. The pandemic effect on core macroeconomic variables like investment, employment, prices (both food & non-food prices), import, export and fiscal policy indicators was estimated and forecasted using Dynamic Stochastic General Equilibrium (DSGE) Model. The role of fiscal policy in mitigating the shock effect of coronavirus pandemic on macroeconomic stability is also investigated. The finding of the study reveals that the COVID-19 impact lasts at least three years to shake the economy of Ethiopia. Given that the Ethiopian economy heavily relies on import to supply the bulk of its consumption and investment goods, COVID-19 uncertainty effect starts as supply chain shock, whose effect transmitted into the domestic economy via international trade channel. The pandemic uncertainty shock effect is also expected to quickly transcend to destabilize the economy via aggregate demand, food & non-food prices, investment, employment and export shocks. The overall impact of COVID-19 pandemic uncertainty shock is interpreted into the economy by resulting under consumption at least in the next three years since 2020. Therefore, the government is expected to enact incentives/policy directions which can boost business confidence. A managed expansionary fiscal policy is found key to promote investment, employment and to stabilize food & non-food prices. A particular role of fiscal policy was identified to stabilizing food, transport and communication prices. The potency of fiscal policies in stabilizing food, transport and communication prices go in line with the prevailing reality in Ethiopia where government has strong hands to control those markets directly and/or indirectly. This suggests market failure featuring COVID-19 time, calling for managed interventions of governments to promote market stabilities. More importantly, price stabilization policies of the government can have spillover effects in boosting aggregate demand by spurring investments (and widening employment opportunities) in transport/logistics, hotel & restaurant, culture & tourism and export sectors in particular.